Blessing and breaking: a dissonance of action and interpretation in the Eucharistic Prayers of the Roman Rite - O'Loughlin, Thomas (The Society for Liturgical Study, 2013)
The references to 'blessing' and 'thanking' in the context of the community meal, the Eucharist, are found in the Synoptic Gospels as referring to Jesus' prayer to God; however, they are interpreted in contemporary Catholic practice as referring to the food items of the meal. This sets up a dissonance between the words used in the liturgy and the liturgical actions that accompany those words.